Water pricing as a means to ensure water conservation: a case study from Palestine - Rabi A. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
In most developing countries, water management has reached its limit at the centralized level. Water supply infrastructure has been developed to serve large portions of the population in these countries including Palestine. It is now the task of local governments to provide their citizens with potable water at a price that people can afford, and at a price that will create revenue stability for the utilities in charge of supply and distribution while ensuring water use efficiency and revenue redistribution. What this demands is a pricing scheme that needs to be tailored to the social, economic, environmental and political situation of the respective country. In the West Bank, water supply management is highly scattered and is not well organized. There are many actors charged with the task of supplying water for the communities. In addition, the current situation of most of the water utilities in the West Bank reveals that the financial inefficiencies that they are faced with are partly due to the economic hardship facing people as a result of the political situation and partly ascribable to unclear pricing policies. The current paper is based on a research conducted by PHG on developing a sound pricing policy in Palestine.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)